Revolution of 1848 in the Italian Kingdoms - Khudair, Dr. Narjis Karim (Thi Qar Arts Journal, 2023)
The Vienna Congress created an undesirable situation for many peoples of the European continent, especially those who lost their freedom under the umbrella of legitimacy, and the principle of compensation that was called for by the major countries present at the conference, which ignored the principle of the right to self-determination that was called for by the French Revolution previously, as most of the peoples, especially those who were suffering under the yoke of the reactionary authority, aspired to establish their own political entities and create their national state, and the Italian kingdoms and regions came at the forefront, as they united history, civilization and language, as well as geographical characteristics that qualify them for union under a unified political system, and if they did not initially decide the nature of that system that they seek to achieve, their first goal was to get rid of the external control represented by the Austrian Empire, which intensified its control and its reactionary methods in dealing with the lands that were administered by it directly or indirectly, so efforts were combined to achieve that goal, but the lack of prior coordination and the lack of national sense among many, and the pursuit of each kingdom to be the leader of the unity prevented the achievement of the final victory, which facilitated the matter for the Austrian forces to eliminate the revolution that broke out in 1848 to include various cities and regions of the Italian peninsula, and the situation returned to its previous state, but that did not mean that it was able to eliminate the national feeling among the free Italians, but on the contrary, it increased it, to be embodied after several years by the complete unity.